Speech By YBhg Tan Sri Professor Emeritus Anuwar Ali, President/Vice Chancellor Open University Malaysia At A Dinner Hosted By Hon. Susil Premjayanth M.P., Minister Of Petroleum Industries, Sri Lanka - Anuwar Ali, (2013)
A speech by YBhg Tan Sri Professor Emeritus Anuwar Ali at Hotel Galadari, Colombo on 30 January 2013.